Peningkatan Hasil Belajar Peserta Didik Pada Keterampilan Menyimak Menggunakan Model Quantum Teaching Berbantuan Media Wordwall di Kelas IV SDN 42 Talawi Pesisir Selatan - Novita, Ratna Sari; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
This research is motivated by the less than optimal planning and implementation of learning carried out by teachers in listening skills, which has an impact on the low learning outcomes of students in class IV SDN 42 Talawi Pesisir Selatan. This study aims to describe the improvement of student learning outcomes in listening skills with the Quantum Teaching Model assisted by Wordwall media in class IV SDN 42 Talawi Pesisir Selatan. The subjects of this study were teachers and 9 class IV students. The approach used was a qualitative and quantitative approach. This type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle includes four stages, namely planning, implementation, observation, and reflection. Data collection techniques include interviews, analysis documents, observations, tests, and non-tests. The results of the study on student learning outcomes obtained the following scores: a) Cycle I obtained a score of 66.5 (D), b) Cycle II obtained a score of 84.2 (B). Based on these results, it can be concluded that the Quantum Teaching model assisted by Wordwall media can improve student learning outcomes in listening skills.